EXPERIENCE WITH Ponseti Protocol and Achilles Tenotomy in THE MANAGEMENT OF Clubfoot at the Lagos STATE UNIVERSITY TEACHING HOSPITAL, lagos, Nigeria - ADEWOLE, 0A (J West Afr Coll Surg, 2017)
BACKGROUND: Achilles tenotomy is very frequently performed to correct persistent equinus deformity in Ponseti clubfoot management worldwide. AIM: To review the frequency of Achilles tenotomy and outcome of treatment of idiopathic clubfoot using the Ponseti method. SETTING: Lagos State University Teaching Hospital, Lagos, Nigeria. DESIGN OF THE STUDY: Prospective observational study METHODOLOGY: All the patients with idiopathic clubfoot treated using the Ponseti protocol in the clubfoot clinic between June 2013 and October 2015 were recruited. The data obtained included biographic data, Pirani score at presentation, number of casts until initial correction, number of feet that had Achilles tenotomy and complications. They were recorded in the International Clubfoot Registry (ICR) hosted by the Centre for Bioinformatics and Computational Biology at the University of Iowa, USA and were analysed using the ICR software. RESULTS: Of the 124 patients in this study, 77 (62.1%) had bilateral foot deformities (154 feet) and 47 patients (37.9%) had unilateral clubfoot making a total of 201 clubfeet. Their ages at presentation ranged from 1 week to 6 years. Forty (32.3%) patients were aged less than 1 month, 58(46.8%) aged between 1 and 6 months, 12 (9.7%) aged between 6 and 12 months and while 14 (11.3%) aged 12 months and above. There were 77 males and 47 females with a male/female ratio of 1.6:1. The initial Pirani score was 4 and above in 140 feet with a mean of 4.3. Correction was achieved after a mean of 5.2 casts and tenotomy was performed in 45 (23.1%) feet before foot abduction brace application. CONCLUSION: This study has shown that congenital idiopathic clubfeet can be managed with good outcome using the Ponseti protocol with a reduced frequency of Achilles tenotomy.